PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENCURIAN BUAH KELAPA SAWIT - Syarif Khadis; Bagio Kadaryanto; Sandra Dewi (LPPM STIH Awang Long, 2025)
Law enforcement against the criminal offense of oil palm fruit theft in Rokan Hulu Regency demonstrates the importance of synchronizing technical guidelines such as Supreme Court Regulation (Perma) Number 2 of 2012 with higher-level legal instruments, particularly the latest Criminal Code (KUHP). Hans Kelsen’s theory of the hierarchy of norms emphasizes that the validity of lower-level norms must conform to higher-level norms, so that law enforcement officers can perform their duties in a fair, effective, and legally consistent manner. This research is expected to serve as a reference for updating guidelines on the handling of minor criminal offenses, ensuring their alignment with the development of national law and the needs of society. This study is a sociological (empirical) legal research. The findings indicate that law enforcement against oil palm fruit theft in Rokan Hulu Regency through Supreme Court Regulation Number 2 of 2012 has been relatively successful in accelerating case resolution and in applying the principles of restorative justice. Mediation and compensation agreements have proven to be effective mechanisms for cases involving low economic losses, while simultaneously reducing the burden on the courts. Nevertheless, the effectiveness of law enforcement remains constrained by weak coordination among law enforcement agencies and related institutions, public perceptions regarding minor criminal offenses, and limited public understanding of legal procedures. The obstacles in law enforcement against the criminal offense of oil palm fruit theft based on Supreme Court Regulation Number 2 of 2012 in Rokan Hulu Regency include limitations in evidence and documentation, constraints in resources and capacity of law enforcement officers, and inconsistencies between legal norms and the socio-economic conditions of the community. Efforts to overcome these obstacles may be pursued through a progressive legal approach and the consistent application of restorative justice, which are more responsive to social realities while still upholding legal certainty and justice.